Borrowing Agreement with Banca d'Italia. (Policy Papers; Policy Paper, 2011)
In light of the multilateral effort to ensure the adequacy of the financial resources available to the International Monetary Fund (the "Fund"), and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance to its members, Banca d'Italia agrees to lend to the Fund an SDR-denominated amount up to the equivalent of EUR 8.11 billion, on the terms and conditions set out below...